Mental Health of High-Risk Urban Youth: The Housing Subsidies Paradox - Musa, George J. (Race and social problems, 2021)
Housing subsidies, including public housing and Sect. 8 vouchers, are key components of the social safety net, intended to promote family and child welfare. Studies evaluating the impact of housing subsidies on child and adolescent mental health, however, are generally inconclusive. This may reflect variation in the influence by type of subsidies to income, improved physical environment, increased access to resources, and improved perception of neighborhood safety. Further, most prior research focused on housing subsidies failed to simultaneously formally assess child psychopathology. In the present study, we examine, among adolescents (ages 9–17) from a low-income, urban minority area, the association of housing with psychiatric symptoms and disorders, as well as with their social functioning. The data were obtained from the Stress & Justice Study (S&J) baseline survey, an investigation designed to examine impact of parental criminal justice system involvement (CJSI) on their children’s mental health. Housing type during the past year was categorized from parental report as public housing, Sect. 8, both, or neither. Child mental health was assessed with the Diagnostic Interview Schedule for Children (DISC). Additionally, family resources and physical quality of the housing environment by housing type was assessed, and we tested whether these dimensions mediated associations of housing type with the adolescent’s current mental health outcomes. We found that while internalizing and externalizing disorders and impairment were attenuated by individual characteristics (e.g., SES, CJSI), internalizing and externalizing symptom counts were significantly more prevalent among children in subsidized housing, compared to those in non-subsidized housing, after controlling for individual characteristics. These findings have the potential to inform whether, and through which mechanisms, housing subsidies are associated with adolescent mental health.